The Correlation between EFL Students' Self Efficacy and Their Speaking Ability - Maharani, Ravita (RETAIN : Journal of Research in English Language Teaching, 2022)
Self-efficacy is a crucial aspect of initiating several activities, specifically in terms of public speaking in EFL student learning. Public speaking skills are essential for students to have an adequate speaking skill, while self-efficacy is one of the psychological factors which can influence the student’s achievement in mastering speaking skills. Hence, self-efficacy in English public speaking can be interpreted as students' beliefs about their proficiency to perform public speaking well. This research aims to find a significant relationship between students’ self-efficacy and their public speaking performance in an English learning program. The population of this research is 50 students from one of the High Schools in Lamongan. The research uses the quantitative method to collect, analyze, and interpret the results of the research. Furthermore, it is included in the correlational research, which is a quantitative method formulated to reveal the correlation between two variables. The Pearson product-momentcorrelation coefficient is used in this research by using the SPSS program in processing the data to determine the relationship. The result of this research indicates that the calculation of r for the student’s self-efficacy and their public speaking performance score is .844 which proves that the two variables have a positive relationship. According to the correlation interpretation, it can be stated that the interpretation between variables X (self-efficacy) and Y (public speaking) is considered as a very high correlation (.80 -.999). In addition, from the significance (2 tailed), the researcher acquires the score 0.01 which determines Sig<0.05 so the null hypothesis (H0) is rejected. Therefore, it is clear that a positive correlation was found between students' self-efficacy and their public speaking performance.